Factors associated with HIV risk perception among people who inject drugs: Findings from a cross-sectional behavioral survey in Kermanshah, Iran. (2nd January 2018) - Armoon, Bahram; Noroozi, Mehdi; Jorjoran Shushtari, Zahra; Sharhani, Asaad; Ahounbar, Elahe; Karimi, Salahedin; Ahmadi, Sina; Farhoudian, Ali; Rahmani, Azam; Abbasi, Mohammad; Marshal, Brandon D.L.; Rezaei, Omid; et al.
ABSTRACT: Background: In Iran there are limited data regarding HIV risk perceptions among people who inject drugs (PWID). The objective of this study was to explore HIV risk perception and to examine factors associated with the perception of HIV risk among PWID in Iran. Methods: We surveyed 433 PWID in Kermanshah concerning demographic characteristics, sexual risk behaviors, HIV risk perception, and drug-related risk behaviors in the month prior to the study. Two classes of HIV risk perception (high vs. low) were identified. We used logistic regression to identify factors associated with high HIV risk perception. Result: Of 433 PWID who participated in this study, 36% (95% confidence interval; CI95%: 25.3%, 42.2%) of participants reported high HIV risk perception. Methamphetamine use (adjusted odds ration; AOR = 3.7, p < 0.05), or use of multiple drugs at the same time (AOR = 1.7, p < 0.05) was associated with higher HIV risk perception. Moreover, PWID who were NSP users had 2.8 times the odds of high risk perception compared with non-Needle and Syringe Program (NSP) users (AOR = 2.8) . Conclusion: This study implies that initiating drug use at a younger age, using methamphetamine, polydrug use, and needle- and syringe-exchange program utilization were predictors of higher HIV risk perception among PWID in Iran.